2016
DOI: 10.1007/s13593-016-0398-2
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for efficiency in the broiler chicken: A review

Abstract: Artificial selection of broiler chickens for commercial objectives has been employed at an unprecedented magnitude over the recent decades. Consequently, the number of days, total feed and in turn energy, required to raise a broiler to slaughter weight, have decreased dramatically. Feed provision is the poultry industry's biggest environmental hotspot; hence, understanding the interactions between the birds' genetic change and their energy use efficiency forms the necessary starting point for quantifying and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
120
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 101 publications
(183 reference statements)
1
120
0
4
Order By: Relevance
“…the synthesis of non‐proteinogenic dipeptides. Selection for fast growth and high feed efficiency has been very successful and has resulted in large decreases in the number of days and the amount of feed required to reach market slaughter weight . Effects of this selection on important body composition traits (e.g.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…the synthesis of non‐proteinogenic dipeptides. Selection for fast growth and high feed efficiency has been very successful and has resulted in large decreases in the number of days and the amount of feed required to reach market slaughter weight . Effects of this selection on important body composition traits (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…breast yield, body fatness) are more variable; however, it has in general resulted in leaner animals with higher breast yield, which also depends on the weight of these traits in the composite breeding goals. According to the review by Tallentire et al ., there is some indication that higher protein deposition has been achieved through selection for efficient growth by lowering protein breakdown; however, net protein turnover seems not to be affected. In contrast, Dransfield and Sosnicki showed that protein turnover is higher in muscles of slow‐growing birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was highlighted by Swaggerty et al who reported that chicken genotypes which produce high levels of IL‐6, CXCLi2 and CCLi2 in response to Eimeria tenella infection have reduced lesional scores in the caeca. In Europe, although fast‐growing broiler genotypes are commonly used in poultry production, the use of slower‐growing genotypes is beginning to emerge . However, nothing has been reported regarding immune phenotypes in fast and slow growing broilers in response to Eimeria infection, which may determine whether fast or slow growing broilers may differ in their underlying resistance to Eimeria .…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, although fast-growing broiler genotypes are commonly used in poultry production, the use of slower-growing genotypes is beginning to emerge. [19][20][21] However, nothing has been reported regarding immune phenotypes in fast and slow growing broilers in response to Eimeria infection, which may determine whether fast or slow growing broilers may differ in their underlying resistance to Eimeria.…”
mentioning
confidence: 99%